Kinetics of venom and antivenom serum levels, clinical evaluation and therapeutic effectiveness in dogs inoculated with Crotalus durissus terrificus venom - Sangiorgio, F. [UNESP]; Sakate, M. [UNESP]; Nogueira, R. M. B.; Araújo Junior, J. P. [UNESP]; Chavez-Olortegui, C. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
This work evaluated the clinical and therapeutic aspects as well as serum levels of venom and antivenom IgG by enzyme-linked immunosorbent assay (ELISA) in experimental envenomation of dogs with Crotalus durissus terrificus venom. Twenty-eight mixed breed adult dogs were divided into four groups of seven animals each, Group I: only venom; Group II, venom + 50 ml of anti-bothropic-crotalic serum (50mg) + fluid therapy; Group III, venom + 50 ml of anti-bothropic-crotalic serum + fluid therapy + urine alkalination; Group IV, 50 ml of anti-bothropic-crotalic serum. The lyophilized venom of Crotalus durissus terrificus was reconstituted in saline solution and subcutaneously inoculated at the dose of 1mg/kg body weight. The dogs presented clinical signs of local pain, weakness, mandibular ptosis, mydriasis, emesis and salivation. The venom levels detected by ELISA ranged from 0 to 90ng/ml, according to the severity of the clinical signs. Serum antivenom ranged from 0 to 3ug/ml and was detected for up to 138h after treatment. ELISA results showed the effectiveness of the serum therapy for the venom neutralization.
Keywords: Crotalus durissus terrificus; dogs; clinical signs; ELISA